(untitled) (Psicologia USP, 2004)
This paper outlines the history and evolution of the model of illusion applied to the religious experience, based on conceptions from Freud, Pfister, object relations theorists, Winnicott, Vergote and Rizzuto. It also delineates the possibilities originated by these theoretical contributions, along with their limitations.